The cost of “snubbing”: the effect of parental phubbing on filial piety behavior in children and adolescents - Zhang, Yongxin; Chen, Bingran; Ding, Qian; Wei, Hua (Frontiers in Psychology, 2024)
Background: Although numerous studies have used Chinese samples to examine the consequences of parental phubbing, these studies focused on children's mental health and peer interaction. No research to date has directly explored the association between parental phubbing and child-parent interaction. Since parental phubbing is a way how parents interact with their children (parent-child), it might be associated with the way how children interact with their parents (child-parent), such as filial piety behavior, which prescribes how children behave toward their parents and remains one of the goals of parents in educating their children in modern Chinese society. Based on social exchange theory and social gender theory, this study investigated the impact of parental phubbing on filial piety behavior and tested its mediation of perceived parental rejection, its moderation of gender among children and adolescents.Methods: This study was conducted using a questionnaire method. A total of 753 students from Grade 4 to 9 (Mage = 12.28 years, SD =1.81 years) was surveyed using the Parental Phubbing Scale, Perceived Parental Rejection Questionnaire, and the revised Dual Filial Piety Scale.Results: First, parental phubbing was negatively correlated with reciprocal filial piety (RFP) behavior, but not correlated with authoritarian filial piety (AFP) behavior. Second, perceived parental rejection played a mediating role between parental phubbing and RFP behavior. Third, this direct effect was moderated by gender, in that it was stronger for boys than for girls.These findings suggest that there are intergenerational costs of phubbing, such as reducing children and adolescents' RFP behavior. The present study is the first to combine parentchild interaction in the digital media era (parental phubbing) with traditional Chinese child-parent interaction (RFP behavior), which expands the research topic on the influence of parental phubbing on children and adolescents' psychological development.